Biodegradation of azo dyes by Aspergillus flavus and its bioremediation potential using seed germination efficiency - Amira M. Ghanaim; Omima M. El Mahdy; Heba I. Mohamed (BMC Microbiology)
Abstract The worldwide textile industry extensively uses azo dyes, which pose serious health and environmental risks. Effective cleanup is necessary but challenging. Developing bioremediation methods for textile effluents will improve color removal efficiency. The recent attention to effectively utilizing microbes to convert toxic industrial azo dyes into non-hazardous compounds has garnered significant attention. In the present study, four fungal strains—Aspergillus flavus, Aspergillus terreus, Aspergillus niger, and Fusarium oxysporium—were employed to screen for the degradation and detoxification of azo dyes including congo red, crystal violet, bromophenol blue, and malachite green. After eight days, A. flavus had degraded azo dyes at the maximum proportion. The maximum decolorization (%) was achieved at 50 mg/L of dye concentration, 8 days of incubation, pH 6, 30 °C temperature, sucrose as a carbon source, NaNO3 as a nitrogen source, Ca+2 as minerals, and using static culture. The efficient production of laccases, lignin peroxidase, and manganese peroxidase enzymes by A. flavus proved that the enzyme played a crucial role in decolorizing the harmful azo dyes. The Fourier Transform Infrared spectrometer (FT-IR) data validated the decolorization and degradation process brought on by absorption and biodegradation. Compared to control plants, the results of the phytotoxicity assay showed that the degraded product was less harmful to maize and common bean plant's growth and germination rates. As a result, the findings indicate that A. flavus is a viable option for remediating azo dyes. This aids in the biodegradation of azo dyes found in wastewater.